The Moderating effect of audit quality on the relationship between board attributes and tax avoidance of listed industrial goods firms in Nigeria - Yusuf, Aminu; Ahmed, Murtala; Bello , Sa’idu Ibrahim; Shehu, Babangida; Baffale, Balaraba (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The study examines the moderating effect of audit quality on the relationship between board attributes and tax avoidance of listed industrial goods firms in Nigeria. Data for the study were sourced solely from the secondary sources extracted from annual reports and accounts of the sampled industrial goods firms in Nigeria. The sample size is 11 industrial goods firms out of the 13 industrial goods firms listed on the floor of Nigeria Exchange Group. Panel regression analysis was applied to analyse the data. The study reveals that board size and board independence exert positive and insignificant effects on the cash effective tax rate (CETR). It also finds that gender diversity and board financial expertise depict negative and significant effects on the CETR. The study further reveals positive and significant moderated effects of audit quality on the CETR. The paper recommends that industrial goods firms in Nigeria should conduct a comprehensive assessment of the board size in relation to the firms’ operational complexity and strategic needs and evaluate the effectiveness of board committees and subcommittees in managing tax related matters. Industrial goods firms in Nigeria should also strengthen the roles and influence of independent directors in strategic tax avoidance decisions to enhance objectivity, transparency and effectiveness of each director. Industrial goods firms and Financial Reporting Council of Nigeria (FRCN) should establish a structured nomination process that encourages the inclusion of qualified female directors in the board selection process and consider appointing directors with a strong background in taxation, finance, and accounting profession.